THE EFFECT OF CLAY MINERALS ON DIASTERANE/STERANE RATIOS - SUPERACID EFFECT OF CLAY MINERALS - Van Kaam-Peters H.M.E.; Koster J.; Van der Gaast S.J.; Dekker M.; De Leeuw J.W.; Sinninghe Damste J.S. (My University, 1998)
To examine the effect of clay minerals on diasterane/sterane ratios, the mineral compositions of three sample sets of sedimentary rocks displaying a wide range of diasterane/sterane ratios were analysed quantitatively. Diasterane/sterane ratios do not to correlate with clay content but depend on the amount of clay relative to the amount of organic matter (clay/TOC ratios). This correlation may explain the high diasterane/sterane ratios in crude oils and extracts derived from certain carbonate source rocks. Based on the concentrations of regular and rearranged steroids in the sample sets, it is proposed that diasterenes are partly reduced to diasteranes and partly degraded during diagenesis in a ratio largely determined by the availability of clay minerals. It is suggested that the hydrogen atoms required for reduction of the diasterenes originate from the water in the interlayers of clay minerals.